Hybrid Times Call for Hybrid Measures: Reflecting on the Information Bubbles Phenomenon in Light of the Nature-culture Debate - Machado, Sara Monteiro (Department of Communications, Universitas Islam Indonesia, 2024)
In the digital era, algorithms have assumed a mediation role historically associated with journalism, limiting and prioritizing information in a personalized manner for each user. This curation contributes to the formation of information bubbles that reinforce selection effects and potentially feed preexisting beliefs. Although it is not a consensual view, several authors believe this phenomenon increases polarization, posing significant challenges to democratic discourse and societal cohesion. This paper reflects on information bubbles in the context of Bruno Latour’s and Edgar Morin’s perspectives on the nature-culture dichotomy. Together, these perspectives help us understand the algorithmic personalization of information as a hybrid (arising from the interaction between humans and non-humans) and complex phenomenon (multidimensional, engaging various parts of knowledge), where the central role of non-human actors and the continuous interaction between the whole and the parts are evident. It is concluded that addressing the information bubbles conundrum will require: (1) abandoning simplification and reductionism, while accepting contradiction and controversies, (2) mapping and analyzing the interactions between actors, (3) conducting inter- and transdisciplinary research, and (4) developing hybrid solutions.